Difficulties in Mastering English Grammar Faced by Secondary School Students' (Fifth Islamic Grade) from teachers' perspective - Omar Mahmood Mustafa AL-Okiedy (Zien Journals, 2022)
The current study aims to know the difficulties that Iraqi Islamic students face in understanding the English grammar and the obstacles that face the teachers in teaching the grammar in EFL Iraqi Islamic Schools (Book 5). The sample of the study includes fifteen teachers and the educational supervising (11 boys(56%) and 5 girls(44%) )who are actually teaching English in the selected schools during the academic year 2018-2019 (in the Islamic schools ) in the city of Kirkuk who represent 61.5 % of the total number of teachers' population. A questionnaire has been conducted and applied to the selected sample. The required data are collected and analysed statistically. The study reaches to results such as , most of EFL teachers are satisfied with the materials of (Book5) concerning their; sufficiency, difficulty, authenticity, integration and appropriacy and the most difficult grammar area is the interrogation and the easiest area is sentence patterns. It also state that the activities and exercises included within( Book5) supply pupils with enough practice in the different kind of English grammar . Regarding the obstacles of implementation and problems which the teachers face in teaching grammar in (Book 5) are; the present perfect tense is explained briefly in unit two, in some units the subjects of grammar without exercises or activities , shortage of lesson time in some schools,and lack of charts .
Keywords: activities; present; teachers; obstacles